Patagonicoside A: A novel antifungal disulfated triterpene glycoside from the sea cucumber Psolus patagonicus - Murray, Ana Paula (2001)
A new triterpene glycoside, patagonicoside A (1), has been isolated from the sea cucumber Psolus patagonicus and its structure has been elucidated by 1D and 2D NMR (1H-, 13C-, 1H-1H COSY, HETCOR, COLOC and NOESY spectra), FAB-MS and chemical evidence. Compound 1 is a disulfated tetrasaccharide with a new aglycon moiety. Patagonicoside A (1) exhibits considerable antifungal activity against the pathogenic fungus Cladosporium cucumerinum.